& salt the earth behind you - Naidoo, Prenesa (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
My thesis is a collection of prose pieces in the form of short stories, flash fiction and prose poetry drawing on memory and lived experiences to explore the trauma of death, grief and displacement, solace and the paroxysms of home. As a young woman from an Indian South Africa community, Hindu superstitions and folktales are my second skin, and shape both my worldview and my writing. I am inspired by Lidia Yuknavitch's observation that, "all artists see things that are not there" , and by Dambudzo Marechera's belief that, "Beneath reality, there is always fantasy: the writer's task is to reveal it, to open it out, to feel it, to experience it." In my stories about trauma and grief, I often distort the line between seen and unseen worlds, where, for example, hauntings are taken seriously as lived experiences. I have also been influenced by Han Kang's The White Book, Kali Fajardo-Anstine's Sabrina & Corina, and Sandra Cisneros' The House on Mango Street. Read together, Kang's stand-alone short stories form part of a greater collective 'memory' or 'life'; Fajardo-Anstine's collection illustrates how to write about a specific female Latina community while still telling individual stories; and Cisneros' fragments of memories tell the story of a person's life in narratives which are as long or short as they need to be.
Keywords: Creative writing (Higher education) -- South Africa; South African fiction (English) -- 21st century; South African poetry (English) -- 21st century; Short stories, South African (English) -- 21st century; Diaries -- Authorship; Korean fiction -- 21st century -- History and criticism; Short stories, Argentine -- 21st century -- History and criticism; Arabic fiction -- Palestine 21st century -- History and criticism; Argentine fiction -- 21st century -- History and criticism